Changes in serum potassium concentration in asthmatic and normal subjects during exercise. Issue 7 (July 1989) - Gugger, M
Abstract : Serum potassium concentrations were measured before, during, and after exercise in 32 patients with asthma (12 with exercise induced asthma), and in seven normal subjects. The changes in serum potassium in response to exercise did not differ significantly in the two groups or between those with and without exercise induced asthma. The potassium response to exercise is unlikely to be relevant to the mechanism underlying exercise induced bronchoconstriction.